Plug-and-Play Framework for Assessment of Renewable Energy Community Strategies - J. P. D. Faria; J. A. N. Pombo; S. J. P. S. Mariano; M. R. A. Calado (IEEE Access)
Recent regulatory advancements by the European Union have positioned Renewable Energy Communities (RECs) at the forefront of energy policy discussions, reigniting significant interest and debate within the scientific community. However, despite all the developments, RECs still face several challenges that need to be addressed and researched to ensure their development and economic sustainability. One key challenge is the creation of effective and fair energy-sharing mechanisms. Thus, this study proposes a Home Energy Management System (HEMS) and a Two-Stage Collaborative Energy Management Strategy (TCEMS) to manage a REC based on both technical and economic aspects, promoting an efficient operation that meets both individual and collective requirements. This is a cooperative and collaborative strategy in which renewable energy production resources and storage systems are shared in an integrated and equitable manner, ensuring a fair and balanced distribution of renewable energy within the REC. In the strategy’s first stage, a dynamic Key of Repartition (KoR) is employed to adaptively allocate renewable energy production among REC participants. In the second stage, Mixed Binary Integer Programming (MBIP) is used to efficiently manage energy surpluses and deficits, ensuring their optimal allocation across participants storage systems. To evaluate the proposed strategy’s performance, a one-year computational simulation was conducted, followed by an experimental validation in a pilot REC over a 24-hour period. The results confirmed the effectiveness and robustness of the strategy, indicating reduced dependence on the utility power grid and optimized utilization of local energy resources.